2011
DOI: 10.20450/mjcce.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

Simple and efficient method for detection of traces of rare earth elements in minerals by raman spectroscopy instrumentation

Abstract: As an effort to increase the knowledge about the abundance, distribution and geochemical behaviorof the rare earth elements (REEs), a simple and effective Raman spectroscopic method for detection of REEsin minerals is proposed. The proposed method based on Raman spectroscopy provides a lower detectionlimit for REEs compared to the modern analytical techniques. It could be practiced even in laboratoriesequipped only with FT-Raman instrumentation. This simple, inexpensive, rapid and straightforward Ramanmethod f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…12). 65 The upper spectral region, above 850 cm -1 , exhibited striking similarity to bands attributed to Si-O stretchings. The strongest band at 920 cm -1 was precisely assigned to the symmetric stretching mode of the SiO4 tetrahedra.…”
Section: Almandinementioning
confidence: 84%
See 1 more Smart Citation
“…12). 65 The upper spectral region, above 850 cm -1 , exhibited striking similarity to bands attributed to Si-O stretchings. The strongest band at 920 cm -1 was precisely assigned to the symmetric stretching mode of the SiO4 tetrahedra.…”
Section: Almandinementioning
confidence: 84%
“…How-ever, it was later discovered that these bands were actually caused by laser-induced fluorescence from the presence of rare earth element (REE) impurities in the specimen providing detailed explanation and theoretical background regarding their occurrence. 65 This perplexing situation highlights the possibility of incorrectly assigning certain bands in FT-Raman vibrational spectra, which could lead to erroneous mineral identification. Similar observations have been made in other fields, such as cement minerals, 66 calcium minerals, [67][68][69] dental materials, 70 and bioceramics.…”
Section: Almandinementioning
confidence: 99%
“…A simple and efficient method for the detection of traces of rare earth elements in minerals by Raman spectroscopy was proposed in ref. [36]. It has a lower detection limits for the rare earth traces in minerals (analytically important), but can even be extended to serve as a convenient experiment for undergraduate and postgraduate laboratory courses.…”
Section: Fig 14 the O-h Stretching Region In The Ir Spectrum Of Berylmentioning
confidence: 99%
“…[28] Pretreatment of samples, correction standards and other techniques such as Raman and X-ray fluorescence have also been used to measure REE in geological samples. [29][30][31][32][33] Although the measurement of REE by ICP-MS is demonstrated to be accurate and reproducible, the proper preparation of materials for ICP-MS is crucial for accurate results. A comparative study of REE in geological reference materials using INAA and ICP-MS showed that ICP-MS was more accurate for light REE (La-Gd) compared to heavy REE (Tb-Lu), but determined that INAA produced results closer to literature values and suggested that sample preparation for ICP-MS was the cause.…”
Section: Introductionmentioning
confidence: 99%